Characteristics of Taiwanese patients of PNH in the international PNH registry. Issue 1 (October 2016) - Chou, Wen-Chien; Huang, Wei-Han; Wang, Ming-Chung; Chang, Chao-Sung; Yeh, Shih-Peng; Chiou, Tzeon-Jye; Chen, Yeu-Chin; Lin, Tseng-Hsi; Shen, Ming-Ching
Abstract Background Paroxysmal nocturnal hemoglobinuria (PNH) is a rare and acquired hematopoietic stem cell disease, with florid clinical presentations. Although this disease has been characterized in the western countries, its clinical and laboratory features in Taiwan have not yet been reported. Results As a part of an international prospective, non-interventional, observational registration trial of PNH, we have analyzed 63 patients recruited between 2009 and 2015 in Taiwan, with comparison to the 3857 patients in the rest of the world (ROW). The median age of diagnosis of our patients is 46 (range 9–84), without sex preponderance. While most of the clinical and laboratory presentations of our patients are similar to the ROW, ours have higher lactate dehydrogenase levels, lower hemoglobin, and higher frequencies of symptoms including shortness of breath and erectile dysfunction at the time of diagnosis. The incidence of thromboembolism was not statistically different between ours and the ROW (6.7 % vs 13.5 %, P = 0.178). The patients in Taiwan were treated more frequently with corticosteroid (53.2 % vs 32 %, P < 0.001), but less frequently with cyclosporine/anti-thymocyte globulin and heparin/warfarin, bothP < 0.001). Conclusions This is the first systematic review on the Taiwanese PNH patients. Our analysis would provide key information about our PNH patients and would help understanding the basic characteristics of this rare disease in Taiwan. Trial registration This trial has been registered to ClinicalTrails.govNCT01374360 .